Analisis dan Ekspresi Gerak: Mencari Hubungan Pada “Sonata Romantica Bagain I. Allegro Moderato” Manuel Ponce - Leonard Aldo Prasetyo Sembiring (Universitas Negeri Surabaya, 2022)
This research departs from the difficulty of players in connecting how musical works can inform movements to players, he said on classical guitarist instruments. So it requires a strategy to answer the challenges in the music performance area. So this study requires several processes to connect this, one of which is the positive analysis that will be discussed in this research. The discussion material is limited to romantic to modern music as a golden era of classical guitar, one of which is the work of Manuel Maria Ponce's